A multi-dimensional search for new heavy resonances decaying to boosted W W , W Z , or Z Z boson pairs in the dijet final state at 13 Te - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Bergauer, T; Brandstetter, J; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; Frühwirth, R; Jeitler, M; et al. (The European physical journal. C, Particles and fields, 2020)
A search in an all-jet final state for new massive resonances decaying to W W , W Z , or Z Z boson pairs using a novel analysis method is presented. The analysis is performed on data corresponding to an integrated luminosity of 77.3 fb - 1 recorded with the CMS experiment at the LHC at a centre-of-mass energy of 13 Te . The search is focussed on potential narrow-width resonances with masses above 1.2 Te , where the decay products of each W or Z boson are expected to be collimated into a single, large-radius jet. The signal is extracted using a three-dimensional maximum likelihood fit of the two jet masses and the dijet invariant mass, yielding an improvement in sensitivity of up to 30% relative to previous search methods. No excess is observed above the estimated standard model background. In a heavy vector triplet model, spin-1 Z ' and W ' resonances with masses below 3.5 and 3.8 Te , respectively, are excluded at 95% confidence level. In a bulk graviton model, upper limits on cross sections are set between 27 and 0.2 fb for resonance masses between 1.2 and 5.2 Te , respectively. The limits presented in this paper are the best to date in the dijet final state.
Keywords: Diboson resonances; CMS; Physics; Substructure